A07 Critical consideration of the criteria for the motor diagnosis of huntington disease. (29th August 2012) - Long, JD; Paulsen, JS; Zhang, Y; Kim, JI; Mills, JS; Liu, W; ,
Abstract : Background: Huntington disease (HD) is a fatal inherited disorder with typical onset in adulthood. In research studies of HD, it is necessary to characterise the progression of participants in order to validly interpret results. Aims: A distinction is often made between gene-positive individuals who are displaying hallmark motor signs (manifest HD) and gene-positive individuals who are not (pre-manifest HD). The conventional threshold for this distinction is the highest rating on the Diagnostic Criterion Level (DCL) scale of the Unified Huntington Disease Rating Scale (UHDRS), which constitutes the motor examiner's confidence level of ≥99% for an unequivocal movement disorder (DCL=4). Methods: A study was undertaken to investigate the empirical support for the use of the DCL for manifest HD classification, and alternatives including cutoffs based on the Total Motor Score (TMS) of the UHDRS. Because a gold standard classification does not exist, extreme case/control differences and extreme of the control distribution were used as a guide to selecting cutoffs. Results: The results show that the conventional DCL criteria is too stringent in the sense that (1) cutoffs based on the TMS and the lower DCL confidence level of 90%–99% (DCL=3) both provide a very strong distinction between cases and controls, and (2) the conventional criterion tends to be assigned well after the accelerated deterioration trajectory characteristic of late-stage HD has already commenced. Conclusion: The results suggest that alternate criteria, especially the intersection of DCL ≥3 and TMS cutoffs, might be considered in HD research.